2015
DOI: 10.1007/s11243-015-9926-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and kinetic study of the formation of silver nanoparticles by reduction of silver(I) in the presence of surfactants and macromolecules

Abstract: The kinetics of formation of silver nanoparticles by reduction of silver(I) with galactose were studied spectrophotometrically in the presence of surfactants and chitosan as stabilizing agents. The reaction was carried out under pseudo-first-order conditions by using a tenfold excess of [galactose] over [Ag ? ]. The effects of cetyltrimethylammonium bromide (cationic surfactant) and sodium dodecyl sulfate (anionic surfactant) on the reaction rate have been studied. Chitosan inhibits the rate of reaction by up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Therefore, it can be assumed that in reaction mixture all silver cations formed coordination complexes with chitosan macromolecules and the rate of silver nanoparticles formation did not depend on the concentration of the reagents. It is worth noting that authors [ 49 ] observed the similar data. They showed that in the presence of chitosan in the reaction media, the reduction of Ag + by galactose carried out very slowly and the “absorbance‐time” dependence of Ag nanoparticles formation was also a straight line.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Therefore, it can be assumed that in reaction mixture all silver cations formed coordination complexes with chitosan macromolecules and the rate of silver nanoparticles formation did not depend on the concentration of the reagents. It is worth noting that authors [ 49 ] observed the similar data. They showed that in the presence of chitosan in the reaction media, the reduction of Ag + by galactose carried out very slowly and the “absorbance‐time” dependence of Ag nanoparticles formation was also a straight line.…”
Section: Resultssupporting
confidence: 76%
“…They showed that in the presence of chitosan in the reaction media, the reduction of Ag + by galactose carried out very slowly and the “absorbance‐time” dependence of Ag nanoparticles formation was also a straight line. [ 49 ] As the reaction temperature increased from 60 to 95°C, the rate constant for CS20 enhanced by an almost one order of magnitude: from 0.0019 to 0.012. The reaction rate in the case of CS30 was slower compared to CS20 and the rate constant enhanced from 0.0001 to 0.002 with increasing temperature from 60 to 95°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-order kinetic rate expression ( 1 ) was used to determine the values of rate constant (k) from the slope of the linear plot of versus time (t) 56 . The plots showed the highest value of slope i.e.…”
Section: Resultsmentioning
confidence: 99%
“…AgNPs can be produced by chemical [ 22 , 23 ], physical or biological routes [ 24 , 25 ]. Biological synthesis uses clean routes, without producing toxic residues.…”
Section: Introductionmentioning
confidence: 99%